Nutritional composition, phytochemical, and functional properties of six soybean varieties cultivated in Cameroon - Mildred Washie Tamangwa; Fabrice Tonfack Djikeng; Romelle Dibanda Feumba; Veshe‐Teh Zemoh Ninying Sylvia; Valerie Demgne Loungaing; Hilaire Macaire Womeni (Legume Science, 2023)
Abstract The objective of this study was to evaluate the influence of different varieties on the nutritional composition, phytochemical, and functional properties of selected soybean varieties cultivated in Cameroon. Soybean varieties TGX 1835, TGX 2001‐8DM, MAK SOY 1N, MAK SOY 3N, MAK SOY 4N, and SOUNG PUNGUNG 2400 were collected and analyzed for their nutritional composition (proximate composition and mineral content), oil quality (peroxide, thiobarbituric acid, iodine, and acid values), total phenolic content, and functional properties. Results of the proximate composition showed that soybean varieties MAK SOY 3N, MAK SOY 4N, and TGX 1835 had the highest protein and lipid contents. The calcium and potassium contents were expressively higher in soybean variety MAK SOY 4N. Soybean variety MAK SOY 3N portrayed the best magnesium, zinc, and iron contents. The oils from all the six soybean varieties exhibited very good chemical properties as far as their safety is concerned. TGX 1835, MAK SOY 4N, and SOUNG PUNGUNG 2400 had the highest total phenolic content. The functional properties presented by all six soybean varieties were similar. These new varieties can be exploited for their nutritional and technological properties. The population should be encouraged to produce and consume them.